'Placing' Lay Perceptions of Health and Illness - Litva, Andrea (My University, 1996)
This thesis contributes to a little researched topic in health geography, that of lay perceptions of health and illness and their relationship to space. Informed by a symbolic interactionist perspective, the qualitative method of in depth interviewing is used to access and explore how 53 informants, living in relatively remote towns in Ontario, conceptualize health and illness. In this study, two notions of place are used. Place is used in both its geographic and experiential senses. Place-in-life, defined in the study largely by age, appears to have an influences on how people perceive health and illness. It is speculated that the differences found between the sites are linked to the presence of a papermill as well as the large number of Native Canadians living in Papermill Town. This study used the theory of symbolic interactionism to uncover the meanings that people held about health and illness. Although a relatively new theory to health geography, it was particularly useful for exploring how these meanings impact upon the physical and social bodies interaction with the world and how they contribute to and maintain a person's place-in-the-world.
Keywords: Geography; Geography